Examination of teachers’ emotional intelligence competence perception levels in terms of sportive activity and different variables - Burak Tozoğlu; Sertaç Erciş (Frontiers in Psychology)
IntroductionThis study examines whether teachers’ emotional intelligence (EI) competence perception levels specifically dimensions such as self-regulation, empathy, and social skills—differ according to sports activity and demographic variables. EI plays a crucial role in fostering effective classroom management and teacher-student interaction. It was hypothesized that teachers who engage in both individual and team sports would demonstrate higher levels of emotional intelligence compared to those who do not participate in sports or engage in only one type.MethodUsing a descriptive survey design, data were gathered from 422 secondary school teachers in Erzurum (204 female, 218 male) during the 2023–2024 academic year via the Personal Information Form and the Emotional Intelligence Trait Scale–Short Form (EITS-SF). Statistical analyses included t-tests, ANOVA (with η2), and Pearson correlation.ResultsEI levels did not significantly differ by gender (p = 0.215), age (p = 0.737), service length (p = 0.511), or overall sport participation (p = 0.641). However, participants involved in both individual and team sports reported significantly higher EI scores (M = 88.96, SD = 17.90; p < 0.001, η2 = 0.06).ConclusionCombining individual and team sports may enhance emotional intelligence more than participation in a single type or no activity. Future research should explore the mechanisms behind this interaction and its educational implications.